Hubungan Usia Kehamilan dengan Kejadian Ketuban Pecah Dini di Klinik Fatiha Bangkinang Tahun 2022 - Wahyuni, Ratu Sri; Handayani, Fitri (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
The direct cause of maternal death in Indonesia is 80% due to obstetric complications and 20% due to other causes. Apart from that, there are three main factors that cause 3 maternal deaths, namely, bleeding, hypertension during pregnancy or pre-eclamation and infection. Bleeding occupies the highest percentage of causes of maternal death (28%), eclampsia 24% and infections caused by PROM 11%, while indirect causes are CED 37% in pregnancy, anemia 40% in pregnancy. Premature rupture of membranes (KPD) or premature rupture of membrane (PROM) is the rupture of the amniotic membrane before delivery, can occur in term or preterm pregnancy. If PROM occurs in preterm pregnancy, it is also called preterm premature rupture of membrane (PPROM). Potential complications of PROM that often occur are the risk of infection, umbilical cord prolapse, fetal disorders, premature birth and at 37 weeks of gestation, respiratory distress syndrome complications often occur which occur in 10-40% of newborns. Apart from KPD babies, it is also dangerous for the mother's life, resulting in the mother's death. The aim of this study was to determine the relationship between gestational age and the incidence of premature rupture of membranes at the Fatiha Clinic in 2021. This research design used quantitative research methods with a case control approach. Case samples were taken using total sampling technique and control samples used systematic random sampling. The research was carried out at the Fatiha Clinic. The case population is data from 102 KPD pregnant women and the control population is 645 normal pregnant women who do not have KPD. The research uses a secondary data checklist sheet. Univariate and Bivariate data analysis using the Chi-Squere test. These results show that there is a relationship between maternal gestational age and the incidence of premature rupture of membranes, with a p value at gestational age of 0.002 < 0.05. To prevent the incidence of PROM, it is necessary to improve the quality of ANC services by recognizing complications in pregnancy as early as possible